Radiological comparison of penetrating endplate trajectory versus anterior bicortical trajectory for sacral pedicle screw insertion in posterior lumbosacral interbody fusion - Matsukawa, Keitaro; Kato, Takashi; Fujiyoshi, Kanehiro; Konomi, Tsunehiko; Yanai, Yoshihide; Yato, Yoshiyuki (Journal of Orthopaedic Science, 2022)
The bicortical or tricortical fixation technique with purchase into the anterior sacral wall or promontory has been recommended to achieve rigid sacral pedicle screw fixation, which carries the potential risk of neurovascular injuries. The penetrating endplate screw (PES) technique was proposed as an alternative screw trajectory to facilitate both strong fixation and safety. However, there has been no report on the practical significance of using the PES technique. The aim of the present study was to investigate radiological outcomes using the PES technique for lumbosacral fusion by comparing it with the anterior bicortical technique. The subjects consisted of 44 patients with L5 isthmic spondylolisthesis who underwent single-level posterior lumbar interbody fusion at L5-S using the PES technique (20 patients) or the anterior bicortical technique (24 patients) and were followed up for > 2 years (mean follow-up: 36.6 months). Screw loosening and bone fusion were radiologically assessed and compared between the two groups. Factors contributing to bone fusion were investigated using the following factors: (1) age, (2) sex, (3) body mass index, (4) bone mineral density, (5) screw diameter, (6) screw length, (7) pelvic incidence, (8) crosslink connector, (9) cage material, and (10) sacral screw insertion technique. Respective screw loosening and bone fusion rates were 10.0 and 90.0% using the PES technique and 29.2 and 79.2% using the anterior bicortical technique, with no significant differences between the two techniques. Multivariate logistic regression analysis revealed that the age (odds ratio = 0.87, p = 0.02) and PES technique (odds ratio = 22.39, p = 0.02) were significant independent factors contributing to bone fusion. This is the first study to demonstrate the significance of using the PES technique to improve radiological outcomes. The PES technique could be a valid option for lumbosacral fixation for L5 isthmic spondylolisthesis in terms of improved bone fusion.